2010
DOI: 10.1007/s10646-010-0558-0
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological effects of the aquatic herbicide, fluridone, on male water mites (Hydrachnidiae: Arrenurus: Megaluracarus)

Abstract: The acute toxicities for technical grade fluridone (Sonar™) and the commercial formulation of fluridone (Sonar®AS) were assessed for male water mites (Hydrachnidiae: Arrenurus: Megaluracarus). Signs of toxicity were evaluated by detection of locomotor dysfunction or death after exposure to concentrations of 100,000, 10,000, 1,000, and 100 μg/L of Sonar™ and 10,000, 5,000, 1,000, 100, and 10 μg/L of Sonar®AS in US EPA, moderately hard reconstituted water (MHRW). The median effective concentration (EC50) was 891… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 23 publications
(38 reference statements)
2
12
0
Order By: Relevance
“…In a recent investigation of the toxicity of fluridone on male water mites (Arrenurus sp. ), Yi et al (2011) reported toxicities to technical grade fluridone similar to our Sonar À PR Ò commercial formulation results; however, they found water mites were 60 times more sensitive in tests with another commercial formulation (Sonar À AS Ò ; Table 2). In the context of typical treatment prescriptions for hydrilla, all of the mussel toxicity data generated in tests with Sonar Ò PR, including those generally reported for regulatory purposes (24 h for glochidia, 96 h for juveniles), are two or more orders of magnitude greater than the water column treatment maximum target concentration for Lake Waccamaw (5 mg/L), and are more than three times higher than the maximum label application rate of 150 mg/L (SePRO Corporation 2012).…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…In a recent investigation of the toxicity of fluridone on male water mites (Arrenurus sp. ), Yi et al (2011) reported toxicities to technical grade fluridone similar to our Sonar À PR Ò commercial formulation results; however, they found water mites were 60 times more sensitive in tests with another commercial formulation (Sonar À AS Ò ; Table 2). In the context of typical treatment prescriptions for hydrilla, all of the mussel toxicity data generated in tests with Sonar Ò PR, including those generally reported for regulatory purposes (24 h for glochidia, 96 h for juveniles), are two or more orders of magnitude greater than the water column treatment maximum target concentration for Lake Waccamaw (5 mg/L), and are more than three times higher than the maximum label application rate of 150 mg/L (SePRO Corporation 2012).…”
Section: Discussionsupporting
confidence: 57%
“…The freshwater snail, S. viriginicus, was equally sensitive to the fluridone formulation Sonar À Genesis Ò as juvenile mussels were to the Sonar À PR Ò formulation (Table 1), and much more sensitive than other animals previously tested in commercial formulations of Sonar Ò (Hamelink et al 1986;Paul et al 1994), except for water mites (Yi et al 2011) (Table 2). The reported acute values for Sonar À Genesis Ò were 1.8 mg/L (96-h LC50) for walleye and 3.6 mg/L (48-h EC50) for Daphnia (SePRO Corporation 2011), which are values 3.6 to 7.2-fold higher than the snail 96-h LC50.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, ''inactive'' ingredients in pesticide formulations affect the toxicity of the active ingredient to a specific organism, and sometimes the adjuvants can be more toxic to non-target species than the active ingredients are (Cox and Surgan 2008;Mann and Bidwell 1999;Mullin et al 2015;Surgan et al 2010;Zhu et al 2014). For example, ''inactive'' ingredients found in common herbicide formulations used at label rates can be directly toxic to mites (Cowles et al 2000;Yi et al 2011), honey bees (Ciarlo et al 2011;Zhu et al 2014), aquatic insects (Dunkel and Richards 1998), and soil organisms (Pereira et al 2009). Indeed, the commercial formulation of 2,4-D can be ten times more toxic to late stage tadpoles of at least one frog species (Rhinella arenarum) than the active ingredient (Aronzon et al 2011), due in large part to the use of poly-ethoxylated tallowamine (POEA) as an adjuvant in aquatic herbicides (Howe et al 2004;Mann et al 2009).…”
Section: Introductionmentioning
confidence: 99%